Restaging Abdominopelvic Computed Tomography Before Surgery After Preoperative Chemoradiotherapy in Patients With Locally Advanced Rectal Cancer - Park, Hyo Jung (JAMA Oncol, 2017)
This study examines the association of diagnostic yield and postsurgical recurrence-free survival with restaging abdominopelvic computed tomography performed before surgery after receiving chemoradiotherapy in patients with locally advanced rectal cancer.